Dynamic correlations between hemodynamic, metabolic, and neuronal responses to acute whole‐brain ischemia. (16th September 2015) - Taylor, Jennifer M.; Zhu, Xiao‐Hong; Zhang, Yi; Chen, Wei
<x xml:space="preserve">Abstract</x> Cerebral ischemia sets off a cascade of neuronal and metabolic responses to preserve brain viability. An understanding of the temporal evolution of these changes during and after ischemia, and their correlation with hemodynamic changes, is essential. In this study, a 12‐min whole‐brain ischemia based on the four‐blood‐vessel occlusion model was employed in rats. Using a high‐temporal‐resolution simultaneous 1H–31P MRS acquisition sequence at 9.4 T, we investigated dynamic occlusion and reperfusion responses in cerebral lactate (Lac), phosphocreatine (PCr), adenosine triphosphate (ATP), pH, and blood oxygenation level dependence (BOLD), together with changes in neuronal field potential activity. We reveal tightly coupled dynamics between hemodynamic, metabolic, and neuronal responses to ischemia. Neuronal activity, BOLD, PCr, Lac, and pH changed immediately following occlusion, indicating reduced energy substrates and consumption, and increased glycolysis to maintain cellular ATP levels, which started to decrease 2.2 min after the onset of occlusion. ATP stores were then gradually consumed to maintain a minimum housekeeping neuronal activity level. By correlating dynamic changes of brain activity, BOLD, and energy metabolism, new insights into the brain's survival ability and mechanisms during an acute ischemic attack from the perspectives of cerebral metabolism, neuroenergetics, and neuronal activity were gained. Copyright © 2015 John Wiley & Sons, Ltd.